Ruído – linguagem - interdisciplinaridade: a anatomia do ruído na arte contemporânea - Mori-Leite, Thiago (2016)
The development of pictorial art in the early twentieth century is dynamic until his break with the Dadaist Marcel Duchamp urinal. throughthe audiovisual language its had continuation in a new hybrid language, wich it will be deified by Futurism Italian artists who will recognize in the new language a mimesis of his new world. The futurist Luigi Russolo is regarded as an artist pioneer in research, trials and uses noise as a major element in his artistic praxis that transcends the avant-garde movement of Italian Futurism and presents resignified throughout the different art forms of the twentieth century. Before Russolo write The Art of Noisesin 1913, noise as element was already present in some way in the arts pictorial post Impressionists of the late nineteenth century and the beginning of the modernist avant-garde, such as the Cubist collages of George Braque and clearly in the draft redefinition of appreciation, enjoyment and production of art designed by Marcel Duchamp. Both conceptually and formally the importance of using the noise can be synthesized in the proposals of the Italian Futurists, adopting noise like a strong aesthetic element that can be found throughout interdisciplinarity that provides it. However, in Luigi Russolo noise is studied and used beyond the aesthetic or semiotic fields, noise becomes a vital practice of the artist, increasingly used and is embodied in the research and work of iconic artists such as the south korean Nam June Paik, pioneer of videoart and the new yorker band Sonic Youth, that among all recording and video production controlled by the cultural industry of the 90's, stands out for using the noise in a intersemiotic way, exploring the relationship between the audio and visual languages, seeking to create a common thread, a structure that aligns the different artistic productions that allied art to technology in early last century.